Cochlear implants in Latin America - Berruecos, Pedro (Auditio, 2021)
Audiology is a relatively young science. However, although it was born in the middle of the 20th century, many medical and technological achievements had been made to deal with hearing loss already by then. Audiology systematized programs and made them grow, rapidly developing diagnostic, research and prosthetic equipment. Day by day we got to know and understand better the wonder that is the sense of hearing: from simple pure-tone audiometry we went on to study many functions: the auditory system with impedance; of the neuro-logical transmission of signals, with the evoked potentials; of the very fine cochlear function, with the otoacoustic emissions and of the auditory perception of the language, with the participation of Linguistics, Imaging and Nuclear Medicine. The huge, uncomfortable, and heavy hearing aids of the 1950s became miniaturized, digital systems that process and amplify acoustic signals in ways as surprising as they were unimaginable half a century ago. In this context, Cochlear Implants (CI) have allowed us to provide useful acoustic information to the profoundly deaf or hard of hearing. In the last 15 years, CI units with more than 30 years of evolution have become an almost daily practice on a global scale. About 40,000 have been placed and in Mexico, for example, after only 80-100 patients were implanted between 1986 and 1999, the initiation of our multi-institutional program in 2000 has determined that in little more than two years, we have implanted as many patients like those of that long 14-year period. We have witnessed the same dynamism in Latin America, a region with an area of ​​14% and a population of 9% of the world, where more than 500 million inhabitants live. In 1998, we conducted a survey to find out the size of the programs of CI in the region and three years later, in 2001, we repeated it to realize its evolution, with that we can now report data of interest to Spanish speakers who cultivate the field of audiology. According to WHO data, in Latin America there are around 50 million people with some type or degree of hearing problem. Of these, more than a million have profound hearing loss or deafness, congenital or acquired, and at least 200,000 could be considered candidates for HF. In the study, we correlated annual per capita income (HICP) with the number of probable CI candidates in each country. From this emerged the hypothetical number of people whose HICP would cover the comprehensive CI program in the country itself. This number was very high in countries with a large population and average HICP, such as Brazil, Colombia, Mexico or Peru, and less high in countries with better HICP and / or lower population such as Costa Rica, Panama or Puerto Rico. This is relevant because the financing of these programs is a challenge that requires the design of special strategies. In Mexico we structured a multi-institutional group (General Hospital of Mexico, Children’s Hospital and National Institute of Respiratory Diseases), in which we emphasize the selection of candidates, through the “IC PROFILE”. This instrument rates 20 medical, audiological, psycho-pedagogical and psychosocial parameters, with 0-5 points, for a total maximum of 100, with the best candidates being those with the most points. The “IC PROFILE” standardized evaluation criteria and led to a better selection. On the other hand, another instrument, the “III” or “Index of Integration with Implants”, corresponds to the average of the results of ten auditory perception evaluation tests. The correlation of "PROFILE IC" with "III" has given the former a predictive value, in addition to the original selective one. Another important strategy seeks cost reduction. We have gotten support from IC companies; We have symbolic fees in our hospitals, because their objectives are for service and not for profit and we are supported by multiple NGOs. For this reason, the acquisition of HF, the preoperative evaluation, the surgical services and the audiological and post-surgical rehabilitation follow-up, have been increasingly accessible to patients from low socio-economic strata. Between 1998 and 2001, the number of implanted patients grew in Latin America from 784 to 2,389. Although 90% are concentrated in the largest and most populated countries in the area (Argentina, Brazil, Colombia, Mexico, and Venezuela), in that period Cuba, Paraguay, Puerto Rico, and Uruguay began programs. Until 2001, in addition to the small English-speaking Caribbean countries, only Bolivia, El Salvador, Nicaragua and Honduras did not have these programs. We believe that the long preparation and the need to overcome obstacles have allowed our groups to be very solid, both due to the sum of human, technical and material resources, as well as the careful selection of candidates and the rigid evaluation of results. Either way, it is necessary to increase Psychoacoustic, Psycholinguistic, Robotics, Economic and Educational research, to improve diagnostic and evaluation procedures, achieve optimal signal processing, attract the interest of NGOs and official entities and have the best human resources. Only in this way can we obtain the results that our patients expect and the successes that our discipline deserves. In our medical field of Audiology and Phoniatrics we can consider ourselves fortunate, because in it we analyze and try to restore the finest perceptual functions of man and because our field of work, hearing, voice and language, is a loom in which notes and phonemes, fills time and space with sounds. From the first cry to today’s poetry or from the grotesque voice to the perfect modulation of the song, centuries have passed. Speaking is a great gift of nature that man acquires thanks to hearing and it is also more by hearing than by sight that man learns the written code, with which he can cross borders and fly without restrictions in time. CIs in Latin America are therefore promise and challenge, hope and encounter, which facilitate our work. A work that allows the human being to modulate his voice, produce language, read and write, create poetry and sing with the soul, so that he continues to be the best artist of nature, as long as hearing allows him to speak because he lives and live because he speaks.